2022
DOI: 10.21203/rs.3.rs-2377951/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Removal of COD from real oily wastewater by electrocoagulation using a new configuration of electrodes

Abstract: In order to bring the chemical oxygen demand (COD) concentration down to safe levels for widespread use, this study plans to use a state-of-the-art electrocoagulation reactor (ECR) to treat real oily wastewater discharged from the Al-Muthanna petroleum refinery. A One-Side Finned (1SF) cathode tube was positioned between two tubular anodes in the continuous ECR, where the active area of the cathode was much more than its submerged volume. Each of these electrodes was made of aluminum and joined in a monopolar … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Results indicated that increasing flow rate led to a decrease in oil removal efficiency while increasing density and electrolysis time improved efficiency up to 99% (Jasim & AlJaberi, 2023a). Similar studies have shown that employing the electrocoagulation process can reduce other pollutants in oil refinery effluent, with turbidity reduced by 84.5% (AlJaberi et al, 2020), COD by 82% (Jasim & AlJaberi, 2023b), and total dissolved solids (TDS) by 13% on average (Jasim et al, 2023).…”
Section: Electrochemical Processesmentioning
confidence: 84%
“…Results indicated that increasing flow rate led to a decrease in oil removal efficiency while increasing density and electrolysis time improved efficiency up to 99% (Jasim & AlJaberi, 2023a). Similar studies have shown that employing the electrocoagulation process can reduce other pollutants in oil refinery effluent, with turbidity reduced by 84.5% (AlJaberi et al, 2020), COD by 82% (Jasim & AlJaberi, 2023b), and total dissolved solids (TDS) by 13% on average (Jasim et al, 2023).…”
Section: Electrochemical Processesmentioning
confidence: 84%